Umbilical cord arterial blood pH an indicator of rise in cesarean section rate due to false-positive indications by CTG - Ruqiya Rashid,; Bashir, Khushbu; Faizah Mufti, (Asian Journal of Medical Sciences, 2024)
Background: Cesarean section rate is rising globally, now accounting for more than 1 in 5 (21%) of all childbirths. This number is set to continue increasing over the coming decade unless the factors which increase the rate of cesarean section are kept in check. Intrapartum cardiotocography (CTG) has shown a false-positive rate of cesarean section. This has been correlated with neonatal umbilical cord blood pH analysis. Aims and Objectives: (1) Correlation of non-reassuring CTG, resulting in cesarean section with umbilical cord arterial blood pH. (2) To find the false-positive indications of cesarean section due to CTG. Materials and Methods: This observational study was conducted in the Department of Obstetrics and Gynecology of SKIMS, Soura, from September 2020 to July 2022 over a period of 22 months. Women with a gestational age of more than 34 weeks with singleton pregnancy were included in the study. Those with CTG-documented fetal distress were subjected to umbilical cord arterial blood pH monitoring. Results: A total of 85 patients underwent cesarean sections in view of fetal distress documented by CTG, but only 45 neonates had actual distress as documented by umbilical cord blood sampling. Conclusion: Social and non-medical factors no doubt have caused an alarming rise in cesarean sections, but at the same time, there are some iatrogenic causes, namely CTG, which lead to the rise in the cesarean section rate due to false-positive indications. This has been further supported by the fact that the pH of the umbilical cord blood of neonates with intrapartum non-reassuring CTG does not correspond to fetal acidemia in all cases. Hence, a significant number of cesarean sections is being done for false-positive indications.